1928-1929 Wis. Sess. Laws 157, An Act to Create . . . the Statutes, Relating to Machine Guns and Providing a Penalty, ch. 132, § 1 - (:unkn) unknown (General Publisher, 1929)
Prohibited owning, using, or possession a machine gun. Punishable by imprisonment of 1-15 years.
--
Keywords: MACHINE GUN RESTRICTION